Digipreneur education as the solution for smes competition in the digital era - Nugraha, Aryan Eka Prastya (Dinamika Pendidikan, 2016)
The objective of the study was to create the digipreneur educational model for SMEs and analyzed its relationship with the more developed digital business world.Â  It used the descriptive analysis to explore and clarify a phenomenon. One of the analyses was SWOT analysis method which helped to arrange the plan for achieving both short term goals and long term goals. Based on the constructed model of Digipreneur educational model which emphasized on business skills aspects where modern financial skill components and all transactions today were using e-banking. Digital marketing aspect should be given to SME owners since they needed to know that marketing today did not just rely on the physical real world, but in the fierce competition in digital media as the effective and efficient marketing means. SMEs were resilient business units in anything economic conditions because of their local resources and they had more significant marketing opportunity if their creative products or services were known through the information technology; thus, they needed to get the information technology education.